Patient Satisfaction Survey for the Telemedicine Services during the Second Wave of the COVID-19 Pandemic in the Homoeopathic Research Institutes of West Bengal - Bhattacharjee, Baidurjya; Pal, Partha Pratim; Purkait, Rajib; Chakraborty, Partha Sarathi; Choubey, Gurudev (Homœopathic Links, 2023)
Background Telemedicine was relevant mostly for providing healthcare facilities in rural and distant areas before the coronavirus disease 2019 (COVID-19) pandemic. In India, telemedicine was not ethically and legally recognized until the onset of the COVID-19 pandemic. In March and April 2020, the councils of different systems of medicine published the ethical guidelines for practicing telemedicine. The mitigation measures and fear of infection resulted in increased availing of the facility by the patients especially those who were already under treatment for chronic diseases. The satisfaction of patients availing of telemedicine is essential for improvising such a method of treatment.Method A multicentric cross-sectional study was conducted at two homoeopathic research institutes in West Bengal, India. The patients attending the outpatient department of those institutes were offered to avail telemedicine facilities during the second wave of the COVID-19 pandemic from April to June 2021. The satisfaction of the patient was measured by conducting a telephonic interview, measured on a predefined questionnaire. The calculated sample size was 305 considering the attrition rate of 10%. The sample was selected randomly from the pool of patients who availed of telemedicine during the second wave.Result In this study, initially 305 patients were contacted for evaluating the satisfaction level of their telehealth consultation, out of which 255 patients consented to participate. The mean score of the overall satisfaction of the patients with the telemedicine session was 7.93 ± 1.51(M ± standard deviation). One sample t-test was conducted for responses to every individual question and was significant (p < 0.001). The subgroup analysis shows that overall satisfaction was significantly different between the two institutes (p = 0.03), but other questions did not show any significant difference.Conclusion The survey conducted shows high satisfaction among patients availing the telemedicine facilities at the two homoeopathic research institutes.
Keywords: telemedicine; patient satisfaction; AYUSH; homoeopathy; survey